2018
DOI: 10.1038/s41372-018-0218-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and safety of diazoxide in the neonatal intensive care unit

Abstract: Diazoxide use in NICU settings has increased over time. Infants receiving diazoxide commonly received diuretics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
(56 reference statements)
1
41
1
Order By: Relevance
“…In a paper describing the pharmacokinetics of diazoxide from Kizu et al [14], a high incidence of hypertrichosis in 17 out of 19 patients was reported, but no major SAEs. In the recent analysis of the use of diazoxide in NICUs by Gray et al [18], they found that pulmonary hypertension occurred in 2% of patients treated with transient neonatal hypoglycemia and that worsening of fluid overload and worsening respiratory status occurred in 14 and 12% respectively. This is a different group of patients than those reported in our paper because only 68 of 868 patients who were discharged home remained on diazoxide.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a paper describing the pharmacokinetics of diazoxide from Kizu et al [14], a high incidence of hypertrichosis in 17 out of 19 patients was reported, but no major SAEs. In the recent analysis of the use of diazoxide in NICUs by Gray et al [18], they found that pulmonary hypertension occurred in 2% of patients treated with transient neonatal hypoglycemia and that worsening of fluid overload and worsening respiratory status occurred in 14 and 12% respectively. This is a different group of patients than those reported in our paper because only 68 of 868 patients who were discharged home remained on diazoxide.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…There is no obvious explanation for why diazoxide would cause necrotizing enterocolitis, so we feel in these circumstances, it is likely not related to the drug. Gray et al reported 1% rate of necrotizing enterocolitis in their 1,066 babies but felt the diazoxide was not causative and that many factors were likely to be in play, specifically all but one of their patients who got necrotizing enterocolitis were < 37 weeks gestation [18]. …”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations